Concentration‐discharge relationships derived from a larger regional dataset as a tool for watershed management. Issue 8 (27th September 2021) - D'Amario, Sarah C.; Wilson, Henry F.; Xenopoulos, Marguerite A.
Abstract: Concentration‐discharge (C‐Q) relationships have been widely used to assess the hydrochemical processes that control solute fluxes from streams. Here, using a large regional dataset we assessed long‐term C‐Q relationships for total phosphorus (TP), soluble reactive phosphorus (SRP), total Kjeldahl nitrogen (TKN), and nitrate (NO3 ) for 63 streams in Ontario, Canada, to better understand seasonal regional behavior of nutrients. We used C‐Q plots, Kruskal‐Wallis tests, and breakpoint analysis to characterize overall regional nutrient C‐Q relationships and assess seasonal effects, anthropogenic impacts, and differences between "rising" and "falling" hydrograph limbs to gain an understanding of the dominant processes controlling overall C‐Q relationships. We found that all nutrient concentrations were higher on average in catchments with greater levels of anthropogenic disturbance (agricultural and urban land use). TP, SRP, and TKN showed similar C‐Q dynamics, with nearly flat or gently sloping C‐Q relationships up to a discharge threshold after which C‐Q slopes substantially increased during the rising limb. These thresholds were seasonally variable, with summer and winter thresholds occurring at lower flows compared with autumn and greater variability during snowmelt. These patterns suggest that seasonal strategies to reduce high flows, such as creating riparian wetlands or reservoirs, in conjunction with reducing related nutrient transport during high flows would be the most effective way to mitigate elevated in‐stream concentrations and event export. Elevated rising limb concentrations suggest that nutrients accumulate in upland parts of the catchment during drier periods and that these are released during rain events. NO3 C‐Q patterns tended to be different from the other nutrients and were further complicated by anthropogenic land use, with greater reductions on the falling limb in more disturbed catchments during certain seasons. There were few significant NO3 hydrograph limb differences, indicating that there was likely to be no dominant hysteretic pattern across our study region due to variability in hysteresis from catchment to catchment. This suggests that this nutrient may be difficult to successfully manage at the regional scale.